2011
DOI: 10.1111/j.1399-0039.2011.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐reactive epitope determination with HLAMatchmaker and its clinical applications

Abstract: Antibodies against allogeneic human leukocyte antigen (HLA) molecules are important impediments to the success of different clinical procedures including transplantation and platelet transfusion. In these settings, characterization of the repertoire of immunogenic epitopes is important for permissible mismatch determination and the identification of acceptable mismatches for sensitized patients. HLAMatchmaker is a computer algorithm that considers small configurations of polymorphic residues referred to as epl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 69 publications
0
52
1
1
Order By: Relevance
“…[21][22][23][24][25] For HLA class II, structural variability has been extensively studied in the context of solid organ transplantation, with some in silico models predictive of antibody formation and/or kidney transplant outcome already entered into clinical use. 26, 27 These models did not prove equally valid for HCT outcome prediction, 23,28 probably reflecting the more complex nature of HLA-peptide recognition by the T-cell receptor (TCR) compared with allo-antibodies. 29,30 Here, we have addressed the functional role of AA polymorphism in HLA class II for clinical outcome of HCT in the context of nonpermissive TCE mismatches at HLA-DPB1, shown by some 4,9 but not all 31 multicenter studies to be associated with mortality after 10/10 HLA-matched unrelated HCT.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] For HLA class II, structural variability has been extensively studied in the context of solid organ transplantation, with some in silico models predictive of antibody formation and/or kidney transplant outcome already entered into clinical use. 26, 27 These models did not prove equally valid for HCT outcome prediction, 23,28 probably reflecting the more complex nature of HLA-peptide recognition by the T-cell receptor (TCR) compared with allo-antibodies. 29,30 Here, we have addressed the functional role of AA polymorphism in HLA class II for clinical outcome of HCT in the context of nonpermissive TCE mismatches at HLA-DPB1, shown by some 4,9 but not all 31 multicenter studies to be associated with mortality after 10/10 HLA-matched unrelated HCT.…”
Section: Introductionmentioning
confidence: 99%
“…Certain antibodies are specific for single eplets [5], but recent studies have also demonstrated that epitopes defined by eplet pairs always involve 1 nonself eplet and a self eplet shared between the immunizing antigen and the antibody producer [5,14,15]. The activation of self-HLA-specific B cells by a nonself eplet may require that the remainder of the structural epitope of the immunizing antigen has considerable structural similarity with 1 of the antibody producer's alleles [16].…”
Section: Discussionmentioning
confidence: 95%
“…18,20 The use of HLAMatchmaker enables identification of these epitopes and allows clear definition of acceptable and unacceptable mismatches for virtual crossmatching. 18 The apparent multiple specificities detected in the sera of our patient can be explained by an antibody reacting to the single mismatched DQ epitope 60QF of the liver donor.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent typing for DQA1 revealed the patient to be DQA1 à 01, à 01, but the liver donor was DQA1 à 01, à 02 ( Table 1). Analysis of polymorphic amino acid residues 18 showed that DQA1 à 02 shares epitopes with DQA1 à 03, à 04, à 05, à 06, which are absent on DQA1 à 01 ( Table 3). As the DQA1 chain is in strong linkage disequilibrium with the DQB1 chain, the identification of antibodies to a shared epitope on DQA1 à 02 to à 06 explains the panel-reactive cytotoxicity to DQ2, DQ3 and DQ4.…”
Section: Case Reportunclassified